Fin des infrastructures, mobilités et nouvelles dynamiques territoriales : le cas de la fermeture de la centrale électronucléaire Superphénix (Isère, France). - Romain Garcier; Paul-Etienne Pini (VertigO)
This article analyzes the closure of the Superphénix fast breeder plant in Creys-Malville, decided in 1997 after 11 years of operation. The Superphénix plant is the only case of a complete closure of a full-scale nuclear power plant in France. It provides information on post-closure territorial trajectories in areas where the nuclear power industry provided many well-paid jobs and significant local tax revenues. In order to document the territorial transformations following the closure, we look into mobilities, based on two sources of data: on the one hand, a quantitative study of residential and professional mobilities that uses the population census (1990, 1999, 2012) and allows us to show the transformation of the employment area around Creys-Malville and the evolution of the socio-economic polarization of the territory; on the other hand, a qualitative study of thirty-one interviews conducted during a field survey in 2012 with territorial actors (residents, mayors, industrialists), which allow us to relate the effects of the closure and the induced mobilities to actors' statements. The article shows how the effects of territorial dereliction feared by the opponents of the closure did not occur: the closure of the site was compensated by new residential and professional mobilities, made possible in particular by the development of the industrial zone of the Ain plain east of Lyon.